Long-lived mesoscopic entanglement outside the Lamb-Dicke regime. - McDonnell, M; Home, J; Lucas, D; Imreh, G; Keitch, B; Szwer, D; Thomas, N; Webster, S; Stacey, D; Steane, A (2007)
We create entangled states of the spin and motion of a single 40Ca+ ion in a linear ion trap. We theoretically study and experimentally observe the behavior outside the Lamb-Dicke regime, where the trajectory in phase space is modified and the motional coherent states become squeezed. We directly observe the modification of the return time of the trajectory, and infer the squeezing. The mesoscopic entanglement is observed up to Deltaalpha=5.1 with coherence time 170 micros and mean phonon excitation n = 16.